Optical approach to analysis of interaction of gallium nitride and weak magnetic fields - Red'ko, R.A. (Functional Materials, 2015)
The long-term transformations of optical transmittance of GaN epitaxial structure under weak magnetic field treatment (B = 60 mT, f = 10 Hz, τ = 1.2 ms, t = 10 min) were obtained. Optical measurements were performed in the waverange of 320-1100 nm at 300 K. The method with three layers simulation was proposed for transmittance spectrum fitting. It was found that the treatment results in not only the optical film thickness changing, but probably in its refractive index too. Non-monotonous changes of the optical thickness, which formed interference, were obtained. Interpretation of the experimental results is based on diffusion of point defects after destruction of the metastable complexes from inner boundaries to surfaces of the studied structures.